A feminist approach to contemporary female Kenyan cinema: Women and nation in From a Whisper (Kahiu, 2008) and Something Necessary (Kibinge, 2013). (1st October 2015) - Giruzzi, Clara
This article addresses depictions of women in relation to nation in two contemporary Kenyan films made by women: From a Whisper (Wanuri Kahiu, 2008) and Something Necessary (Judy Kibinge, 2013). The analysis of the films is located within the theoretical framework of African feminism. Using textual analysis as its main method, this article argues that these films convey an African feminist sensibility. This is revealed in the contextualised women's issues that the films address, in their equalitarian representation of men and women as identifiable through their common humanity, and in their pacifist messages about conflict resolution and forgiveness. Moreover, this article intends to show that these films successfully tie the personal to the political, as individual stories of Kenyan women are intertwined with national events and post-trauma national reconstruction. Thus the films highlight the role of women in nation-building, to which the film-makers themselves contribute.